Intervensi Casework Berbasis Asesmen Partisipatif pada Korban KDRT: Praktik Pekerjaan Sosial di BKKBN Provinsi Sumatera Utara - Dede Khairunnas; Fajar Utama Ritonga; Agus Suriadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Domestic violence (DV) has serious impacts on the psychological, social, and economic conditions of victims. This study aims to analyze the casework assistance process for an adult female victim of DV conducted during a Field Work Practice at the National Population and Family Planning Board (BKKBN) of North Sumatra Province. The research employed a qualitative approach with a single case study design. The participant was a 35-year-old female DV victim. Data were collected through in-depth interviews, participant observation, and documentation. The assessment integrated the three-round Delphi Method and Venn Diagram to map the client's barriers and potentials. The results showed that the client experienced severe psychological pressure, economic dependence, and limited access to services. The casework intervention, which included emotional support, self-esteem enhancement, victim rights education, and facilitation of formal services, successfully fostered positive changes, reflected in increased courage, improved family communication, and better understanding of available protection services. This study contributes to the development of social work practice in handling DV cases within family resilience institutions.